Overexpression of S4D Mutant of Leishmania donovani ADF/Cofilin Impairs Flagellum Assembly by Affecting Actin Dynamics - Kumar, Gaurav (American Society for Microbiology, 2012)
Leishmania, like other eukaryotes, contains large amounts of actin and a number of actin-related and actin binding proteins. Our earlier studies have shown that deletion of the gene corresponding to Leishmania actin-depolymerizing protein (ADF/cofilin) adversely affects flagellum assembly, intracellular trafficking, and cell division. To further analyze this, we have now created ADF/cofilin site-specific point mutants and then examined (i) the actin-depolymerizing, G-actin binding, and actin-bound nucleotide exchange activities of the mutant proteins and (ii) the effect of overexpression of these proteins in wild-type cells. Here we show that S4D mutant protein failed to depolymerize F-actin but weakly bound G-actin and inhibited the exchange of G-actin-bound nucleotide. We further observed that overexpression of this protein impaired flagellum assembly and consequently cell motility by severely impairing the assembly of the paraflagellar rod, without significantly affecting vesicular trafficking or cell growth. Taken together, these results indicate that dynamic actin is essentially required in assembly of the eukaryotic flagellum.